Design and simulation electric skateboard / Muhammad Iqbal Haziq Abdullah - Abdullah, Muhammad Iqbal Haziq (2022)
As a result of the environmental disaster, the ozone layer is thinning day by day, and nonrenewable resources take a long time to recover and are becoming increasingly expensive. As a result, electric cars are a superior option since they are more convenient, offer more functionalities, and are potentially more dependable. They are environmentally friendly since they may obtain energy from natural resources that are abundant and freely available. It is accessible to everyone. Noise pollution and vibration are also reduced.